The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3846/13923730.2014.945953
|View full text |Cite
|
Sign up to set email alerts
|

Application of Delphi Method in Construction Engineering and Management Research: A Quantitative Perspective

Abstract: Abstract. The Delphi method has been used as a main research method by a growing number of researchers in the Construction Engineering and Management (CEM) field in the past two decades. Although a number of studies are available on the use of Delphi, few researchers fully examine the potential of the Delphi method in the combined use of statistical techniques, which is an inevitable trend for future Delphi research. This paper aims to review the combined use of Delphi and other quantitative methods in the CEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
196
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(201 citation statements)
references
References 95 publications
2
196
0
3
Order By: Relevance
“…To look into possible differences in RC values between green and traditional residential building construction projects, the Wilcoxon signed-rank test was conducted. This method is a non-parametric statistical test to compare two sets of scores that come from the same participants, without requiring the data must be normally distributed [51]. In this study, test results showed that the p-values of 35 risks were less than 0.05, suggesting there were significant differences in RC values of the most risks between green and traditional residential building construction projects.…”
Section: Risk Criticalities: Green Versus Traditional Residential Buimentioning
confidence: 77%
“…To look into possible differences in RC values between green and traditional residential building construction projects, the Wilcoxon signed-rank test was conducted. This method is a non-parametric statistical test to compare two sets of scores that come from the same participants, without requiring the data must be normally distributed [51]. In this study, test results showed that the p-values of 35 risks were less than 0.05, suggesting there were significant differences in RC values of the most risks between green and traditional residential building construction projects.…”
Section: Risk Criticalities: Green Versus Traditional Residential Buimentioning
confidence: 77%
“…However, the key concerns for the moderator focus on two aspects: (1) what extent the consensus can really reach up to, namely the consensus level is the actual issue the moderator cares about; and (2) how much the moderator needs to cost for reaching a consensus, i.e., the negotiation cost. Available research about consensus measure, including qualitative judgment methods (Skinner et Akiyama et al 2016), mainly focused on a single distance-based measurement of the consensus level.…”
Section: Introductionmentioning
confidence: 99%
“…Each item of the questionnaire is assessed by an evaluator team with a minimum value representing the evaluators' most "conservative cognitive value" (C i ) of the item, and a maximum representing the most "optimistic cognitive value" (O i ). [63,64], is used in FDM, which is an attractive characteristic of the method. With a limited sample size, FDM can build consensus despite different perspectives from the participants while obtaining a reliable and objective opinion.…”
Section: Fuzzy Delphi Methods (Fdm)mentioning
confidence: 99%
“…Repeat the calculation for the tree scores of ", i.e., minimum ( ), geometric mean ( ), and maximum scores ( ). (3) Examine whether evaluators' judgments converge using A small sample size, mostly between 15 to 20 [63,64], is used in FDM, which is an attractive characteristic of the method. With a limited sample size, FDM can build consensus despite different perspectives from the participants while obtaining a reliable and objective opinion.…”
Section: Fuzzy Delphi Methods (Fdm)mentioning
confidence: 99%
See 1 more Smart Citation